2022
DOI: 10.4103/1735-5362.359431
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new small molecules as dual FoxM1 and Hsp70 inhibitors using computational methods

Abstract: Background and purpose: FoxM1 and Hsp70 proteins are highly expressed in many cancers. Thus, their inhibition serves as Bonafede targets in cancer treatment. Experimental approach: FDI-6, an inhibitor of FoxM1, was selected as a template, and based on its structure, a new library from the ZINC database was obtained. Virtual screening was then performed using the created pharmacophore model. The second virtual screening phase was conducted with molecular docking to get t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Interestingly, it was found that down-regulation of HSP60 provoked by IGFBP7 may trigger IGFBP7's tumor-suppressive natural behavior in CRC ( 23 ). It was also reported that HSP70 plays a significant role in the suppression of the apoptosis pathway ( 24 25 ). The findings of the current study highlighted that KKA significantly up-regulated the expression of IGFBP-2 and IGFBP-6 while down-regulating the expression of IGF-1, HSP60 as well as HSP70 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was found that down-regulation of HSP60 provoked by IGFBP7 may trigger IGFBP7's tumor-suppressive natural behavior in CRC ( 23 ). It was also reported that HSP70 plays a significant role in the suppression of the apoptosis pathway ( 24 25 ). The findings of the current study highlighted that KKA significantly up-regulated the expression of IGFBP-2 and IGFBP-6 while down-regulating the expression of IGF-1, HSP60 as well as HSP70 proteins.…”
Section: Discussionmentioning
confidence: 99%